MENGULIK KONSEP NEGARA MENURUT PEMIKIR ISLAM PERIODE KLASIK, PERTENGAHAN, DAN MODERN - Dian Pertiwi; Jamal Mirdad; Mami Nofrianti (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: Islam as a religion that comes from Allah does not only talk about the problems of ubudiyah and the hereafter, but also talks about various aspects of life, including governance. However, it is recognized that it is strictly and clearly not found the concept of government or caliphate in Islam, let alone the concept of the state in the sense of nation-state. Understanding the concept of the state will feel more complicated when we include various points of view and perspectives. Because the order to establish a state will not be found in the literature of the Holy Qur'an and the Hadith of the Prophet. However, when we want to know the organs of this country, we find many in the Al-Quran and Hadith. Islam is a cooperative religion, discussing all issues, both ukhrawi and worldly problems. From this worldly discussion, it will definitely discuss constitutional issues including discussing the issue of the concept of the state according to Islam. The purpose of this research is to add and enrich the knowledge about the state as a positive side.Keywords: Concept, State, Islamic Scholar